Pseudomonas aeruginosa: a pathogen making itself at home. Issue 7 (July 2022) - Stölting, Helen; Lloyd, Clare M.
Abstract : Upon bacterial infection, mounting the appropriate immune response is paramount to effective pathogen clearance. In a recent study, Agaronyan et al. show how Pseudomonas aeruginosa can divert host immunity to boost type 2 responses and drive mucus production, which can then act as a nutrient source for bacteria.